Siblings of children with autistic spectrum disorders 1 - Siegel, Bryna (Henry Stewart Talks, 2012)
Siblings of Children with Autistic Spectrum Disorders, Age and gender of siblings Prototypes for sibling coping, Autism and siblings stressors, Coping with ASD in family context, Coping influenced by child and parent characteristics, Autistic spectrum disorders are a syndrome, Inside the world of the autistic spectrum child, Autism as seen by sib in different ages, The impact of ASD on parents and siblings, A child with an ASD is a 'life event', Diagnosis of autism, The grief process, Outcry, Denial, Intrusion, Working through, Stasis vs. chronic sorrow, Implications for the family